Animal-Type Melanoma - a Mini-Review Concern-ing One of the Rarest Variants of Human Melanoma - Roncati, L; Piscioli, F (Klinicka onkologie, 2018)
The authors declare they have no potential conflicts of interest concerning drugs, pro-ducts, or services used in the study. The Editorial Board declares that the manu-script met the ICMJE recommendation for biomedical papers. Submitted: 17. 6. 2017 Accepted: 1. 11. 2018.
Keywords: nádory kůže; Melanosis; melanóza; Humans; Nevus, Blue; Skin Neoplasms; lidé; Rare Diseases; vzácné nemoci; Melanoma; modrý névus; melanom